2020
DOI: 10.3390/toxins12060369
|View full text |Cite
|
Sign up to set email alerts
|

Exoenzyme Y Contributes to End-Organ Dysfunction Caused by Pseudomonas aeruginosa Pneumonia in Critically Ill Patients: An Exploratory Study

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that causes pneumonia in immunocompromised and intensive care unit (ICU) patients. During host infection, P. aeruginosa upregulates the type III secretion system (T3SS), which is used to intoxicate host cells with exoenzyme (Exo) virulence factors. Of the four known Exo virulence factors (U, S, T and Y), ExoU has been shown in prior studies to associate with high mortality rates. Preclinical studies have shown that ExoY is an important edema factor in lung in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…ExoY is the second most prevalent exotoxin, expressed by >89% of isolates [ 113 , 120 ]. It is a soluble adenylate cyclase that elevates the intracellular levels of various cyclic nucleotides (cAMP, cCMP, cGMP, and cUMP) when injected into mammalian cells, activating protein kinases [ 117 , 121 ].…”
Section: Pseudomonas Aeruginosa Virulence Factomentioning
confidence: 99%
See 1 more Smart Citation
“…ExoY is the second most prevalent exotoxin, expressed by >89% of isolates [ 113 , 120 ]. It is a soluble adenylate cyclase that elevates the intracellular levels of various cyclic nucleotides (cAMP, cCMP, cGMP, and cUMP) when injected into mammalian cells, activating protein kinases [ 117 , 121 ].…”
Section: Pseudomonas Aeruginosa Virulence Factomentioning
confidence: 99%
“…It is a soluble adenylate cyclase that elevates the intracellular levels of various cyclic nucleotides (cAMP, cCMP, cGMP, and cUMP) when injected into mammalian cells, activating protein kinases [ 117 , 121 ]. Consequently, it causes irreversible actin microtubule disassembly, cell necrosis, and alteration of endothelial barrier integrity, following lung injury and end-organ dysfunction [ 120 , 122 ]. Recently, it was shown that ExoY possesses one actin-binding site that directly bundles actin filaments in the host cell [ 123 ].…”
Section: Pseudomonas Aeruginosa Virulence Factomentioning
confidence: 99%
“…At lower ExoY concentrations, which are more likely during chronical infection, the activity of PaExoY allows P. aeruginosa to hijack host immune response by a suppression of TAK1 and a decreased production of interleukin 1 (9,10). A recent report has established a link between the presence of PaExoY in clinical isolates and end-organ dysfunction in critically ill patients (11).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent study genotyping P. aeruginosa isolates from 99 critically ill, mechanically ventilated patients, showed a 93% prevalence of the exoY gene. GC activity was verified in vitro from six of the exoY encoding P. aeruginosa isolates by measuring cGMP accumulation in infected cells (Wagener et al, 2020).…”
Section: Discussionmentioning
confidence: 99%